2013
DOI: 10.1590/s0104-12902013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Impasses no processo de regionalização do SUS: tramas locais

Abstract: Deadlocks in the process of health regionalization: local plots Impasses no processo de regionalização do SUS: tramas locais 49 AbstractRegionalization of the public health system aims to encourage and enhance efforts and measures involving the organization of local and regional public health, through coordinating all those involved. The barriers that often hinder the process of regionalization are linked to tensions and conflicts between objectives, integration and political factors. This article intends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…In addition, these councils have a greater dialogue with the population of the region and social movements, so that they take part of the territory where they live and participate in the construction of regional development [16][17] . From this perspective, it is understood that the regional consciousness and identity encompasses the identification of inhabitants with their region, both within and outside of it [18][19][20] . Studies show the positive effects of regional governance when it is culturally appropriate and participation is equitable, although it seems always difficult learning the needs of stigmatized and poor populations 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these councils have a greater dialogue with the population of the region and social movements, so that they take part of the territory where they live and participate in the construction of regional development [16][17] . From this perspective, it is understood that the regional consciousness and identity encompasses the identification of inhabitants with their region, both within and outside of it [18][19][20] . Studies show the positive effects of regional governance when it is culturally appropriate and participation is equitable, although it seems always difficult learning the needs of stigmatized and poor populations 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A implementação do SUS não foi acompanhada por mudanças nos métodos e estruturas das organizações de saúde (MENDES, 1996). O principal exemplo dessa rigidez de estruturas está diretamente relacionado com o espaço de atuação regional que são as instâncias regionais das SES, quase sem função, a não ser como repassadores de papel dos níveis centrais para os municípios e espaços de barganha política (SILVA;GOMES, 2013). (1996) falou de descentralização, referiu-se a poder, capacidade de decisão, e não apenas de descentralização de responsabilidades.…”
Section: Resultsunclassified
“…However, neither the CIR documents nor the managers' speeches contained proposals aimed at addressing or equating the aforementioned management challenges and strengthening -or establishing -the inter-municipal links required for regionalization. The inadequacies of this institutionality are not prerogatives of the regional study; they have been identified as a current relevant characteristic of the ongoing national regionalization [24][25][26] process, although it seems more pronounced in the North region.…”
Section: Mr "X" Indicated That There Is a Future Intention To Promotmentioning
confidence: 99%